All work and no play ; Where little things count ; On our own [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1993)
Interview with working children, victims of child labor in Youngs Town and Capital Refinery in Cainta, Rizal. KY, an organization of the Graduate School Volunteer group in Ateneo work with cancer afflicted children. McKintosh Production on Les Miserables staged in the Philippines by Filipino performers.
All work and no play (17 min.) -- Where little things count (16 min.) -- On our own (16 min.)
VHS.
Reporters, Marga Ortigas, Luchi Cruz-Valdes.
Keywords: Hugo, Victor Marie Conte, 1802-1885. -- Adaptations; Children -- Employment -- Philippines; Sick children -- Psychology. -- Philippines; Children -- Hospital care; Musicals; Paris -- Social life and customs -- 19th century -- Fiction